Faktor-Faktor Yang Berhubungan Dengan Kesembuhan Penderita Baru TB BTA Positif Di Kota Yogyakarta Tahun 2011 - Ana Susanti; Tuntas Bagyono; Bambang Suwerda (Sanitasi: Jurnal Kesehatan Lingkungan, 2012)
WHO declared tuberculosis (TB) as global emergency. In 2004, TB cases in Indonesia was esti-mated as much as 539.000 with 140.000 death every year. Based on the evaluation of the im-plementation of TB controlling program, in Yogyakarta City in 2011, two of national indicators had been achieved, i.e. Case Detection Rate and Error Rate. Meanwhile, several factors were suspected as the cause of the fail of the Recovery Rate and the Conversion Rate met the nation-al targets. This study was aimed to analyze factors related with the recovery of new positive BTA cases in Yogyakarta City by conducting survey which followed cross sectional design. As the respondents were 60 new cases of the post-medication program derived from 18 puskesmas throughout the city and sampled by using proportional cluster random sampling method. Data were collected by conducting interview, observation and measurement. Univariate, bivariate and multivariate analysis were employed to reveal the dominant factors. Bivariate analysis of Odds Ratio found that among the observed variables, house illumination and medication compliance were correlated significantly with the recovery of new cases. However, advanced multvariate analysis by conducting logistic regression test only found the medication compliance as the do-minant factor.